Human Health Threat and Economic Vulnerability: A Case Study on the COVID-19 Pandemic - Alamsyah, Mirah Satria; Alfian, Muhammad Faizal; Darussalam, Miftah Farid (UI Scholars Hub, 2021)
This paper frames the approach to determining policies in response to the COVID-19 pandemic, which either prioritise human health security protection or economic vulnerability. In this paper, the human security concept will be used to explain COVID-19 as a health security problem due to the existence of an existential threat. However, the same approach is not applicable in looking at COVID-19 as an economic security problem. Because the existential threat is less visible in human economic security aspects, it tends to be more appropriate to look at COVID-19 as the stressor that strengthens human vulnerabilities. This paper uses a qualitative descriptive approach by using the conceptual framework to analyse news, reports, books, and academic journals as the sources of data. The writers analyse and group the data by types of security, as well as based upon the root causes that contribute to human vulnerability, then compare both sectors. This paper argues that in the pandemic situation, human health is threatened, whereas the economy is at a vulnerable position due to COVID-19. This paper also argues that COVID-19 has not yet threatened human economic security in the early stage, but soon, it will. As a result, stakeholders need to prioritise policies based on the human health security approach.